The Special Process of Early Termination in the New Criminal Procedure Code - Robles Sevilla, Williams Alexander (2015)
The termination of the process is a mechanism for procedural simplification has been fully regulated by the Criminal Procedure Code of 2004, but that is not new to our legal system and applied it to certain crimes-money launder in gand customs-. His addition to our criminal justice system responds to achieve greater speeding solving criminal cases because of the crisis being experienced by our justice system that results in an excessive increase in the caseload and criminal political guide lines from reforms Latin American process are from the 90’SA trend in the region. The incorporation of early termination should not only beseen from the dogmatic frame work but also from the practical, which is why we must pay attention to the numbers in the districts whereit has been applied and there by contribute to solutions that are not only in the paper.